Epidermolytic Hyperkeratosis With Digital Contracture - Bhat M Ramesh; Mathew Deepa; Martis Jacintha (Wolters Kluwer Medknow Publications, 2002)
We report a case of epidermolytic hyperkeratosis with digital contracture. The patients had hyperkeratotic lichenfified lesions over extensive areas on the body.